How well do organizations understand the knowledge that could be lost. - Marta Mancilla (International Journal of Management, Knowledge and Learning, 2022)
Purpose: The purpose of this study is to identify the type of knowledge considered the most critical knowledge available in each organizational management level, as well as the knowledge at-risk in Mexican organizations by the different management levels.